2008
DOI: 10.1073/pnas.0803029105
|View full text |Cite
|
Sign up to set email alerts
|

Embedded cholesterol in the nicotinic acetylcholine receptor

Abstract: The nicotinic acetylcholine receptor (nAChR) is a cation-selective channel central to both neuronal and muscular processes and is considered the prototype for ligand-gated ion channels, motivating a structural determination effort that spanned several decades [Unwin N (2005) Refined structure of the nicotinic acetylcholine receptor at 4 Å resolution. J Mol Biol 346:967-989]. Purified nAChR must be reconstituted in a mixture containing cholesterol to function. Proposed modes of interaction between cholesterol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
97
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(103 citation statements)
references
References 42 publications
4
97
2
Order By: Relevance
“…Indeed, the identification of a steroid-binding site between M4 and M1-M3 in the mouse GABA A receptor, as well as a similar modulatory site in the rat ␣7 nAChR, appear to support this (38,39). Simulations have also hinted that a similar site might exist for cholesterol in the Torpedo nAChR (28).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Indeed, the identification of a steroid-binding site between M4 and M1-M3 in the mouse GABA A receptor, as well as a similar modulatory site in the rat ␣7 nAChR, appear to support this (38,39). Simulations have also hinted that a similar site might exist for cholesterol in the Torpedo nAChR (28).…”
Section: Discussionmentioning
confidence: 84%
“…One possibility is that lipids disrupt these inter-domain interactions by altering the packing of transmembrane helices. Transmembrane helix packing could ultimately dictate the conformation of the M2-M3 and ␤10-M1 linkers, thereby influencing crucial interactions at the interface between the transmembrane pore and agonist-binding domains (28).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have indicated the need for Chol to maintain AChR conformation and function (10). Recent dynamic in silico molecular simulations of AChR suggest that the structure collapses in the absence of Chol (52). Hence, Chol depletion could also be associated with changes in AChR conformation, making it more sensitive to internalization.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have concluded that neutral and anionic lipids are both essential, with considerable research focusing on the role of Chol (6,8,37). It has been suggested that Chol and anionic lipids influence nAChR secondary (38,39) or tertiary/quaternary structure (26,40). The implication is that lipids are required for the nAChR to "fold" into a native conformation.…”
Section: Discussionmentioning
confidence: 99%